Effect of Theory-Centered Educational Program on Prostate Cancer Preventive Behaviors among Male Teachers: A Quasi-Experimental Study - Alireza Didarloo; Siamak Shekhi; Zahra Sorkhabi; Naser Sharafkhani (Iranian Association of Health Education and Health Promotion, 2016)
Background and objective: After cardio-vascular diseases, cancers are the most important causes of mortality among the human society. Prostat cancer is one of the most common cancers and is also the second factor that causes mortality among male people after repiratory cancer. The aim of this study was to evalute the educational intervention program based on Health Belief Model (HBM) on prostat cancer preventive behaviors. Methods and material: This quasi-experimental study was carried out on 100 male teachers in Urmia, Iran. The samples were selected via multistage random sampling method. The study data was gatherd using a three-part instrument including demographic information, HBM constructs questionaire, and health performance questionaire. This questionnaire was completed by teachers before and 3 months after intervention. The data was analysed using descriptive statistics, independent and paired t-test through SPSS 20. Results: The mean age among intervention and control groups were 46.2±3.63, 45.5±3.10, respectively. Before intervention, there was no significant difference between two groups in terms of mean scores of the model constructs and health performance (p > 0.05). After intervention, mean scores of perceived suceptibility, perceived severity, perceived benefits, perceived barriers, perceived self-efficacy, and health performance changed. These changes were statistically significant among intervention and control groups (p < 0.001). Conclusion: Educational intervention based on HBM was effective on prostate cancer preventive behaviors. Therefore it is recommended that health educators use model-based instructional plans instead of traditional educational programs. Paper Type: Research Article.